Synthesis and in vitro investigation of halogenated 1, 3‐bis(4‐nitrophenyl)triazenide salts as antitubercular compounds. (14th September 2017) - Torfs, Eveline; Vajs, Jure; de Macedo, Maíra Bidart; Cools, Freya; Vanhoutte, Bieke; Gorbanev, Yury; Bogaerts, Annemie; Verschaeve, Luc; Caljon, Guy; Maes, Louis; Delputte, Peter; Cos, Paul; et al.
Abstract : The diverse pharmacological properties of the diaryltriazenes have sparked the interest to investigate their potential to be repurposed as antitubercular drug candidates. In an attempt to improve the antitubercular activity of a previously constructed diaryltriazene library, eight new halogenated nitroaromatic triazenides were synthesized and underwent biological evaluation. The potency of the series was confirmed against the Mycobacterium tuberculosis lab strain H37Ra, and for the most potent derivative, we observed a minimal inhibitory concentration of 0.85 μm . The potency of the triazenide derivatives against M. tuberculosis H37Ra was found to be highly dependent on the nature of the halogenated phenyl substituent and less dependent on cationic species used for the preparation of the salts. Although the inhibitory concentration against J774A.1 macrophages was observed at 3.08 μm, the cellular toxicity was not mediated by the generation of nitroxide intermediate as confirmed by electron paramagnetic resonance spectroscopy, whereas no in vitro mutagenicity could be observed for the new halogenated nitroaromatic triazenides when a trifluoromethyl substituent was present on both the aryl moieties. Abstract : Halogenated 1, 3‐Bis(4‐Nitrophenyl)triazenide salts were synthesized and tested in vitro against Mycobacterium tuberculosis . The compounds showed selective activity towards Mycobacterium tuberculosis and Staphylococcus aureus but were unable to inhibit the growth of Escherichia coli, Salmonella typhimurium, Pseudomonas aeruginosa and Candida albicans . The trifluoromethyl substituent proved crucial to prevent the metabolization of the compounds into gentoxic metabolites in vitro.